Evaluating and classifying the impact of individual risk on the delayed EPC hydropower projects in the developing countries of Asia. (15th July 2019) - Mai, Sy Hung; Siphada, Vatthanaly; Wang, Jianqiong; Mekthanavanh, Vinath; Hlaing, Htay Htay; Sokliep, Pheng
Many hydropower projects in the developing countries of Asia have currently adopted the project delivery method of engineering, procurement and construction (EPC). However, the EPC general contractors are facing many difficulties, resulting in schedule delays and considerable cost overrun. The purpose of this research is to evaluate the risks causing schedule delays of EPC hydropower projects in the developing countries of Asia. The study analysis and assessment of risks is based on survey questionnaires, which achieved the follow findings: (1) there are 21 main risks influencing on schedule delays; (2) scientifically rank the influence of every single risk on schedule delays; (3) provide a recommendation that could reduce or eliminate these risks on schedule delay of EPC hydropower projects. This study provides a valuable reference which helps investors and contractors finish on schedule to ensure the benefits when building EPC hydropower projects in the developing countries of Asia.